Psychometric Analysis and Factorial Invariance of the Self-Report of Assertive Behavior (ADCA-1) in Peruvian Adolescents - Huamani-Cahua, Julio Cesar; Ojeda Flores, Estefany; Chocano Rosas, Teresa Jesus; Rivas Vargas, Úrsula; Bustamante Gamarra, Moisés; Soncco Huilcahuamán, Vilma; Ojeda Flores, Michael Antony (Interacciones, 2025)
Introduction: Assertive behavior in adolescence is important for well-being and socio-emotional functioning, therefore having valid instruments that are comparable across subgroups is essential. The Assertive Behavior Self-Report (ADCA-1) is frequently used, but its structure and equivalence across gender and age in adolescent populations require further evidence. Objective: To determine the psychometric properties and factorial invariance of the Assertive Behavior Self-Report (ADCA-1) in adolescents. Method: An instrumental design was used, with a non-probabilistic intentional sample consisting of 229 students aged 14 to 17 years (M = 15.44; SD = .82), 50.7% were male and 49.3% female. The instrument used was the Assertive Behavior Self-Report (ADCA-1). Results: Data were analyzed through a CFA for polychoric matrices and a WLSMV estimator, finding a two-factor model with 20 items, well-fitted, self-assertiveness and hetero-assertiveness. Internal consistency was adequate for both factors (self-assertiveness α = .749, ω = .747; hetero assertiveness α = .782, ω = .783). In addition, factorial invariance was confirmed by gender and age, which allowed comparisons between groups. In the comparisons, significant gender differences were found, with higher scores in female adolescents. No differences were observed as a function of age. Conclusion: The findings support the validity and reliability of the ADCA-1 for use in adolescents and in comparative studies; it is suggested to extend the evidence with convergent validity and temporal stability in more diverse samples.